A Constitutive Model for the Creep Behavior of Offwhite Marbles (Advances in Applied Mathematics and Mechanics, 2012)
This paper reports an improved constitutive model for the shear creepbehavior of offwhite marbles which are selected from slope and underground cavern and contain green schist's weak structural planes. The shear creep behavior ofthe samples is characterized using the rheological tests. Based on the experimentalmeasurements on mechanical properties under different normal stress conditions,an improved model is proposed to analyze the experimental results. It is demonstrated from a further discussion that such model can reflect the non-linear creepcharacteristics of structural planes, and especially, it is suitable for description ofthe viscoelastic and viscoplastic deformation behavior of structural planes.